Pseudoscorpions (Arachnida) from Argentina. New records of distributions and habitats, corrections and an identification key - Mahnert, Volker; Iorio, Osvaldo Di; Turienzo, Paola; Porta, Andres (Zootaxa, 2011)
Seventy-two named species of Pseudoscorpiones, representing 14 families, are recorded from Argentina, of which Chernetidae (40 species) and Withiidae (11 species) are the most diverse. Three species are new country records: Parachernes melanopygus, P. plumosus and P. peruanus. The provincial distributions and habitat preferences of the species are given and discussed. Synonymies, old combinations and misidentifications (only those concerning Argentina), original localities, number of specimens, instars and repositories are given (when known), along with new provincial records, localities and habitats, and a key to the families, genera and species known from Argentina.